WORKHSOP IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI PADA KURIKULUM MERDEKA DI MTs ATTARAQQIE MALANG - Wafiyatu Maslahah; Lailatul Rofiah; Adzimatnur Muslihasari; Fitrotul Ainiyah; Maulina Arofati Zuhro; Nindia Rosa Nirmada (Bajang Institute, 2024)
Workshop activities on the Implementation of Differentiated Learning in the Independent Curriculum at MTs Attaraqqie Malang to increase teachers' knowledge and understanding regarding its implementation. especially in terms of differentiated learning. The number of activity participants was 17 people consisting of leaders and teachers from MTs Attaraqqie Putri Malang City. The selection of material was obtained from the results of a questionnaire that was distributed to MTs Attaraqqie teachers. Based on the questionnaire that was distributed, it was concluded that most levels of understanding regarding differentiated learning still need upgrading or training. This activity approach uses a training/workshop model so that improvements related to understanding of differentiated learning in the independent curriculum can be achieved